LoRa-based IoT Device for Water Quality Monitoring (Case Study: Lake Toba) - Gloria Polly, Victori Steev; Manalu, Andriono; Simbolon, Kiki Tristianti; Manalu, Istas Pratomo (Program Studi Teknik Mesin Universitas Pamulang, 2024)
Lake Toba, the largest lake in Indonesia, faces water pollution problems due to many sources of household waste, fertilizer waste from rice fields, and fish feed waste. Therefore, a water quality monitoring system is needed to warn the public and visitors early before they carry out recreational activities or use water from the lake. This research aims to build a system that can monitor the water quality of Lake Toba in real-time using LoRa technology, as well as analyze the water quality of Lake Toba with the parameters pH, dissolved oxygen, temperature, and turbidity. As a result, we created a water quality monitoring system and obtained water quality analysis results from 3 locations that are always busy with tourists. The results of measurements at Pantai Pasir Putih received a temperature range of 25.5°C to 28.5°C, turbidity ranged from 4.1 to 5.5 NTU; pH levels varied between 6.8 to 7.2, dissolved oxygen levels ranged from 8 .0 mg/L to 9.0 mg/ L. The results of measurements at Siregar Aek Nalas recorded temperatures ranging from 25°C to 28°C, turbidity levels of approximately 11.49 NTU and 14.65 NTU, pH levels fluctuating between 9 and 11, dissolved oxygen levels ranging from 29 mg/L to 32 mg/L. The temperature obtained for Pantai Lumban Bulbul was 25°C, turbidity ranged from 0.62 NTU to 2.60 NTU, the pH level was also consistently measured at 8, and dissolved oxygen levels were recorded at 9-10 mg/L.